MODIFIKASI BAJAK ROTARY TRAKTOR RODA EMPAT TIPE ISEKI 504 UNTUK PEMBUATAN BEDENGAN - Bejo Iriyanto; Indah Widanarti; Yosefina Mangera (Musamus AE Featuring Journal, 2021)
This research aimed to modify the rotary plow into a bed-making tool. The performance test of the bed-making tool was carried out on sandy and loamy land by experimental method. The dimensions of the bed including the length, width, and height of the bed as well as the time are also measured in the tool performance test. The bed-making tool has a total length of 182 cm, the length of the right and left sides of each was 51 cm, the width was 25 cm and the height was 30 cm. The test of the bed-making tool by a four-wheel tractor was carried out on sandy land at a distance of 10 m and a loamy land at a distance of 25 m, bed making was performed 5 times. Experimental results on sandy land showed that the average bed height was 23.6 cm; the bottom width was 80 cm, and the top width bed was 56.4 cm with a processing time of 2.12 minutes. Loamy land testing showed that the average bed height was 21.2 cm; the bottom width was 80 cm, the top width was 58.8 cm with a processing time of 4.27 minutes. Based on the test results on two different types of land, it can be seen that the tool works more effectively and efficiently on sandy land than loamy land.